2018
DOI: 10.1080/02699931.2018.1472554
|View full text |Cite
|
Sign up to set email alerts
|

Looking into your eyes: observed pupil size influences approach-avoidance responses

Abstract: The eyes reveal important social messages, such as emotions and whether a person is aroused and interested or bored and fatigued. A growing body of research has also shown that individuals with large pupils are generally evaluated positively by observers, while those with small pupils are perceived negatively. Here, we examined whether observed pupil size influences approach-avoidance tendencies. Participants performed an Approach-Avoidance Task using faces with large and small pupil sizes. Results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…First, different studies demonstrated that eye-related cues are spontaneously considered when acting with a partner (De Stefani, Innocenti, Secchi, Papa, & Gentilucci, 2013;Ferri et al, 2011;Innocenti et al, 2012;Quesque & Coello, 2014). Second, recent works have shown that humans may use others' pupil changes to produce adaptive responses, without any training, when explicitly informed about their importance (Naber, Stoll, Einhäuser, & Carter, 2013) but also spontaneously in the absence of any instruction (Brambilla, Biella, & Kret, 2018;Kret & de Dreu, 2017;Kret et al, 2015;Van Breen et al, 2018). Whether potential partners may interpret high level social information as subtle as the one reported in the current study and adapt their behavior in response is however unknown and represent avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…First, different studies demonstrated that eye-related cues are spontaneously considered when acting with a partner (De Stefani, Innocenti, Secchi, Papa, & Gentilucci, 2013;Ferri et al, 2011;Innocenti et al, 2012;Quesque & Coello, 2014). Second, recent works have shown that humans may use others' pupil changes to produce adaptive responses, without any training, when explicitly informed about their importance (Naber, Stoll, Einhäuser, & Carter, 2013) but also spontaneously in the absence of any instruction (Brambilla, Biella, & Kret, 2018;Kret & de Dreu, 2017;Kret et al, 2015;Van Breen et al, 2018). Whether potential partners may interpret high level social information as subtle as the one reported in the current study and adapt their behavior in response is however unknown and represent avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In a seminal paper, Hess (1965) revealed that male individuals liked women with large pupils better than women with small pupils. In a similar vein, it has been shown that people are more willing to interact when partners have large rather than small pupils (Brambilla et al, 2019). Moreover, individuals with large pupils are judged to be sociable, and trustworthy, and those with small or constricting pupils cold, and untrustworthy (Kret & De Dreu, 2017;Kret, Fischer, & De Dreu, 2015).…”
mentioning
confidence: 90%
“…To manipulate pupil size, we created two stimuli (see Figure 1): in one the image had pupils 40% larger than the standard pupil. In the second, the image had pupils 40% smaller than the standard pupil (see Brambilla et al, 2019;Kret et al, 2015).…”
Section: Experimental Stimulimentioning
confidence: 99%
See 2 more Smart Citations